MCA method in information storage and retrieval - Thanh, Nguyen Chi (Journal of Computer Science and Cybernetics, 2015)
The paper presents one proof of the non-repetition of address for the object in an MCA-method and the unicity of attributed value, which is obtained from the development of address.